Long QT Syndrome in Athletes: Diagnosis, Risk Stratification, and Management for Safe Sports Participation - Piasecka, Natalia; Majewska, Melania; Rafalska, Izabela; Smagoń, Jakub; Kornacka, Natalia; Kaim, Martyna; Bober, Joanna; Bochenek, Magdalena; Siewiera, Wiktoria; Bednarski, Krzysztof; et al. (Quality in Sport, 2026)
Background. Long QT Syndrome (LQTS) is a hereditary cardiac channelopathy that predisposes individuals to malignant arrhythmias and sudden cardiac death. In athletes, physiological cardiac adaptations can mask or mimic LQTS, complicating diagnosis and risk assessment. Methods. This review synthesizes current evidence on the diagnosis, risk stratification, management, and safe sport participation in athletes with LQTS, drawing from cohort studies, clinical guidelines, and expert consensus. Results. Diagnosis in athletes requires careful ECG evaluation, exercise testing, and genetic analysis to distinguish pathological QT prolongation from training-related changes. Risk stratification integrates clinical history, genotype, and monitoring tools, including wearable ECG devices. With appropriate therapy, primarily beta-blockers, and individualized monitoring, many athletes can safely participate in moderate- to high-intensity exercise. Conclusions. Early recognition, structured assessment, and multidisciplinary management enable safe sports participation for athletes with LQTS while reducing the risk of sudden cardiac death. Genotype-specific approaches and continuous monitoring further optimize safety while supporting athletic performance.